The Effect of Student Teams Achievement Divisions (STAD) to the Students’ Writing Ability on Recount Text - Lidia Denta Grace Barus; Herman herman; Khairun Niswa (Journal of English Education and Teaching, 2020)
This research focuses on the effect of Student Teams Achievement Divisions (STAD) to the Students’ Writing Ability on Recount Text at Grade Ten of SMA HKBP 1  Pematangsiantar’. Problem raised in this research was ‘What is the effect of Student Teams Achievement Divisions or STAD on the students’ writing ability at grade ten of SMA HKBP 1 Pematangsiantar’. To answer the problem above, the researchers use the theories of some experts. They are:  Harmer (2004) ,Knapp  & Watkins ( 2005) , Aljanian (2012), Kagan (2009),  Zemach &  Rumisek (2003). The participants were the grade X of SMA HKBP 1 where there are two classes, one is as a control and the other is as an experimental class. The methodology used in this research was the Qualitative research. The data was collected by doing the observation. After the data been collected the researcher found the significant effect of STAD in improving the students’ writing skill. It can be seen from the data where the main score of pretest to post test in experimental class is 56,23 to 80,95. It has a great change. The result showed that the students at grade X of SMA HKBP 1 Pematangsiantar are able to improve their writing skill especially in recount text by applying STAD strategy in the class.